Correlation between C--reactive protein and serum iron levels in children with pneumonia - I Gd. Oki Novi Purnawan; Ida Bagus Subanada; Sri Mulatsih (Paediatrica Indonesiana, 2012)
Background Pneumonia is an infectious disease often occuringin children under five years of age. At the time of infection,pro-inflammatory cytokines are released. It is thought that thesepro-inflammatory cytokines cause changes to iron homeostasisin the body.Objective To determine a correlation between CRP and serumiron levels in children with pneumonia.Methods An analytical, cross-sectional study was performedin children aged 6 months-5 years with severe pneumonia atSanglah Hospital, Denpasar, Bali from April-November 2010.Laboratory examinations included CRP and serum iron levels.The correlation between CRP and serum iron levels was analyzedby Pearson's correlation.Results From 69 children with severe pneumonia, 23 childrenfulfilled the inclusion criteria. Subjects' median CRP level was9.22 mg/Land median serum iron level was 25.55 ug/dL. Thecoefficient correlation between CRP and serum iron levels was-0.580 (P=0.004). The determination coefficient value was0.316.Conclusion In children with severe pneumonia, CRP levelcorrelates negatively with serum iron levels. [Paediatr lndones.2012;52:38-42).